Amino group promoted photocatalytic hydrogen evolution activity observed in two copper(ii)-based layered complexes. Issue 36 (24th August 2018) - Li, Lei; Zhu, Shuang; Hao, Rui; Wang, Jia-Jun; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : The amino group effect of the photocatalyst on the catalytic activity of water splitting was investigated under visible light irradiation. The hydrogen production rate of the amino group modified layered complex is almost double that without the amino group. Abstract : Two copper(ii )-based layered complexes with or without the amino group, [Cu(HL)2 (NH2 -BDC)] n (1 ) and [Cu(HL)2 (BDC)] n (2 ) (HL = 4′-(4-hydroxyphenyl)-4, 2′:6′, 4′′-terpyridine, NH2 -H2 BDC = 2-amino-1, 4-benzenedicarboxylic acid and H2 BDC = 1, 4-benzenedicarboxylic acid), were solvothermally synthesized and used as photocatalysts to accelerate hydrogen production from water splitting. The amino group modified1 has exhibited greatly enhanced photocatalytic activity with a hydrogen production rate of 2.34 mmol g −1 h −1 under visible light irradiation, which is almost double that of2 . Density functional theory calculations, electrochemical impedance spectroscopy and transient photocurrent tests demonstrate that the higher catalytic activity of1 than2 is a result of the enriched electron density around the Cu II center by the amino group, which facilitates the charge transfer from the conduction band to the water molecule.